Assessing Local Small Businesses: A Decision-Making Framework Using the COPRAS Method - Sugiarta, Putu Agus Arya Sastra; Dwijaputra, I Kadek; Putra, Putu Agus Febri Sedana; Ali, Raihan; Sudipa, I Gede Iwan (PT.KARYA GEMAH RIPAH, 2025)
The selection of optimal dining places for students around the INSTIKI campus is often a challenge due to the lack of organized information. This research proposes an evaluation framework using the Complex Proportional Assessment (COPRAS) method, a Multi-Criteria Decision Making (MCDM) approach, to assess and rank restaurants based on various criteria, such as price, food quality, production capacity, distance to campus, and reputation. Data was collected through surveys, field observations, and online reviews, and analyzed using COPRAS. The results showed that the best alternative was Mie Gacoan Pakerisan with the highest utility value (100%). With this approach, students can choose a dining venue that suits their needs, while local small businesses benefit from transparent data-driven evaluation.